Gene Therapy for Gastric Diseases - Fumoto, Shintaro; Nishi, Junya; Nakamura, Junzo; Nishida, Koyo (Current Gene Therapy, 2008)
Gene therapy for gastric cancer and gastric ulcer is a rationalized strategy since various genes correlate with these diseases. Since gene expressions in non-target tissues/cells cause side effects, a selective gene delivery system targeted to the stomach and/or cancer must be developed. The route of vector transfer (direct injection, systemic, intraperitoneal, gastric serosal surface and oral administration) is an important issue which can determine efficacy and safety. Strategies for cancer gene therapy can be categorized as suicide gene therapy, growth inhibition and apoptosis induction, immunotherapy, anti-angiogenesis, and others. Combination of the target gene with other genes and/or strategies such as chemotherapy and virotherapy is promising. Candidates for treatment of gastric ulcer are vascular endothelial growth factor, angiopoietin-1, serum response factor, and cationic host defense peptide cathelicidin. In this review, we discuss stomachand cancer-targeted gene transfer methods and summarize gene therapy trials for gastric cancer and gastric ulcer.
Keywords: Gastric cancer